Confucianism and Feminism in Korean Context. (May 2015) - Kim, Heisook
This paper considers a recent claim that Confucianism and feminism are compatible since both are care ethics. I examine some aspects of contemporary care ethics and compare them with Confucian ethics from a feminist viewpoint. I argue that for Confucianism to be made compatible with feminism, the former must be transformed to the extent that it loses its main features. Care ethics can be feminist ethics only when women have been made moral subjects because of their perceived ability to care for others. Caring in a Confucian culture is not as much a feminine value as a male value. I do not find Confucian ethics as care ethics to be particularly liberating for women. For Confucianism to be viable in a contemporary democratic world, it must be supplemented by feminist ethics that take justice and equality as the primary values.